Evaluation of Musa host plant response using nematode densities and damage indices - Speijer, P.R.; Ssango, F. (1999)
Host plant response of seven Musa accessions to Radophlus similis and helicotylenchus multicintus was evaluated at Namulonge, Uganda.Suckers detached from first cycle harvested plants grown in inoculated and not inoculated fields were indexed for root and corm damage. Nematodes were extracted from the indexed roots. Relationship between root damage parameters and nematodes population densities were examined using correlation and principal component analysis. Damage parameters were of major importance. Three groups of cultivars could be statistically differentiated. The cultivars Gros Michel(Musa AAA), Pisang Awak (Musa AAA) and Obino I Ewai (Musa AAB) were more sensitive and susceptible to nematode attack. Cultivar Nabusa (Musa AAA, highland banana clone set Nfuuka) was intermediate and did not differ significantly from either group.